A Destructive Interaction Mechanism Accounts for Dominant-Negative Effects of Misfolded Mutants of Voltage-Gated Calcium Channels - Mezghrani, Alexandre; Monteil, Arnaud; Watschinger, Katrin; Sinnegger-Brauns, Martina J; Barrere, Christian; Bourinet, Emmanuel; Nargeot, Joel; Striessnig, Jorg; Lory, Philippe (The Journal of neuroscience, 2008)
Channelopathies are often linked to defective protein folding and trafficking. Among them, the calcium channelopathy episodic ataxia type-2 (EA2) is an autosomal dominant disorder related to mutations in the pore-forming Ca v 2.1 subunit of P/Q-type calcium channels. Although EA2 is linked to loss of Ca v 2.1 channel activity, the molecular mechanism underlying dominant inheritance remains unclear. Here, we show that EA2 mutants as well as a truncated form (D I-II ) of the Ca v 3.2 subunit of T-type calcium channel are misfolded, retained in the endoplasmic reticulum, and subject to proteasomal degradation. Pulse-chase experiments revealed that misfolded mutants bind to nascent wild-type Ca v subunits and induce their subsequent degradation, thereby abolishing channel activity. We conclude that this destructive interaction mechanism promoted by Ca v mutants is likely to occur in EA2 and in other inherited dominant channelopathies.